Forgotten Cape – Extremist violence in Northern Mozambique - Károly Gergely (Belügyi Szemle)
Aim: The aim of the study is to provide an overview of the violent extremist insurgency in Mozambique’s Cabo Delgado province with a special emphasis on developments in 2023 and 2024.